Handbook of pathophysiology (Springhouse Corp, 2001)
The Handbook of Pathophysiology is designed for the health care professional who enjoys the challenge of science-based practice. It is an easay-to-use reference that provides a synopsis of updated information on the major pathophysiologic disease processes. This handbook presents more than 450 diseases.